Mudança organizacional: um estudo em empresas graduadas por uma incubadora de biotecnologia - Arimar Colen Gontijo (2004)
This work analyzes the process of organizational change occurred in graduated enterprises which developed from an incubator. Having an ample discussion from different points of view about planned changes and unplanned or emergent changes, an attempt that asks the question:Which are the characteristics of the process of change that suffer a incubated firm during the graduation, from the point of view of the planned organizational change and the emergent change? Some companies which were incubated and graduated during 1999 and 2003 werestudied. The sample was made up of three companies. To collect the data semi-structured interviews were done furthermore some documents of the companies were analyzed. The content of the data was analyzed and checked up on those documents. The categories of analyze were planned organizational change and emergent change. In the scope of the planned organizational change were verified key factors of the theories E and O, a perspective based on the power and influence, organizational structure indicators, organizational processes and technology indicators, people changing indicators. As results this work verified a combine ofthe theory E and O as a better approach, in case of the perspective based on the power and influence none consistent conclusion was made, in the structure a centralization occurred during the transition followed by a decentralization after the graduation, the amplitude of control range between three and twenty employees for managers, procedures and policies support the companies in the transition and departmentalization much more used were functional and by product; technology and procedures must be considered in pairs emphasizing equipment and tools, changes level, started point; necessary time; participation;the risk of change were moderate in ALFA and BETA companies and in BETA was low, so it suggest that incubator can minimize the risk of a organizational change, biotechnology was the main qualifier; finally, as a conclusion the start up companies or companies in transitionemphasizing the structural and cultural changes, the peoples changing help the comprehension that its possible to put in the frame of Lewin (Defrost-Implantation- Refreeze). The programmed and planned face of those business was observed, but some improvisation and surprise situations occurred too, it suggest that more studies have to bedone considering the emergent change in practical way as far as academics.